Teacher Self-Efficacy as a Result of an Agriculture-based Renewable Energy Professional Development Workshop - Paulsen, Thomas H.; Han, Guang; Humke, Sarah J.; Ohde, Nicholaus R. (Journal of Agricultural Systems, Technology, and Management, 2014)
Demand for a modern day workforce well versed in science, technology, engineering, and math (STEM) has been continuously increasing (Pinnell et al., 2013). It is of further concern that the United States is not producing an adequate number of skilled STEM graduates with the knowledge and skills necessary to address problems of the future (Beasley & Fischer, 2012). Since many renewable energy technologies are relatively new and often change (Faunce et al., 2013), it can be difficult for high school and community college instructors to stay abreast of new information in these fields (Zhao & Cziko, 2001). Bandura’s (1997) self-efficacy theory served as the foundation for this study. The purpose of this study was to determine the effectiveness of a renewable energy professional development workshop for high school agriculture and science teachers in altering their science teaching efficacy and outcome expectancy beliefs. The Science Teaching Efficacy Beliefs Instrument (STEBI) (Riggs & Enoch, 1989) was adapted for this study to measure self-efficacy relative to teaching energy-related content. At the end of the workshop, teacher efficacy and outcome expectancy increased from the pre-test to the post-test, however long term increases in self-efficacy were deficient. Science-based professional development workshops have the potential to change in-service teacher behavior in the long-term. However, to secure long-term impacts on self-efficacy, it is recommended that bioenergy workshops offer follow-up support through an electronic community of practice.